Failure analysis of the 13Cr valve cage of tubing pump used in an oilfield. (November 2018) - Long, Y.; Wu, G.; Fu, A.Q.; Xie, J.F.; Zhao, M.F.; Bai, Z.Q.; Luo, J.H.; Feng, Y.R.
Abstract: The 13Cr valve cage of a tubing pump fractured after 191 days service in an oilfield in China. The failure causes were analyzed by direct-reading spectrometer, Rockwell hardness tester, optical microscope, scanning electron microscopy, energy dispersive spectrometer, electrochemical method and finite element method in this paper. The results showed that the failure reason was typical corrosion fatigue fracture initiating at the root of the last thread next to the thread relief groove, where numerous corrosion pits and cracks were observed. In general, co-effect of two factors occurred to cause the valve cage to corrosion fatigue fracture. The downhole medium with high CO2 and Cl − concentrations was the environmental factor of the failure. Alternating stress caused by pumping cyclic motion was the main stress factor of the failure, while the high stress concentration on thread connection further induced cracking. Highlights: Failure reason of the 13Cr valve cage of tubing pump was corrosion fatigue. The passive scales on the surface of the 13Cr valve cage were broken caused by the downhole medium. The last thread and relief groove of thread connection were stress concentrations zones during the upstroke. Pitting corrosion and stress concentrations induced the initiation of fatigue cracks.